Philippines : Are Cash Transfer Programs Effective? - World Bank (Washington, DC, 2015)
Countries around the world increasingly rely on conditional cash transfers to boost health and education outcomes for the poorest citizens. In developing and middle income countries in Asia, Africa, and the Middle East, cash transfer programs are proving effective in a range of areas, including as an incentive to get more girls in school. In the Philippines, the World Bank teamed up with the Government of the Philippines in 2007 to develop the Pantawid Pamilyang Pilipino Program, a conditional cash transfer program for the poor. An impact evaluation was built into the program to measure the effect. Based on the evidence, the Government of the Philippines has increased the cash transfer amount for older students and expanded the program to include children ages 15 to18, who were not previously covered. As policy makers and development experts continue to search for innovative ways to help the world s poor, the findings from this evaluation will provide much-needed evidence for designing increasingly effective programs.